What is the extent of potentially avoidable admissions amongst hospital inpatients with palliative care needs? - Gott, Merryn; Gardiner, Clare; Ingleton, Christine; Cobb, Mark; Noble, Bill; Bennett, Michael I.; Seymour, Jane (BioMed Central, 2013)
Background There is clear evidence that the full range of services required to support people dying at home are far from being implemented, either in England or elsewhere. No studies to date have attempted to identify the proportion of hospital admissions that could have been avoided amongst patients with palliative care needs, given existing and current local services. This study aimed to examine the extent of potentially avoidable admissions amongst hospital patients with palliative care needs.